Experimental and numerical study of forming force in ultrasonic vibration single point incremental forming. Issue 1 (18th August 2022) - Zimeng, Yao; Lang, Bai; Xiaoming, Liang; Shenli, Wu; Ling, Liu
Abstract: A device combining ultrasonic vibration plastic processing technology and single point incremental forming was developed in this work, with maximum power output of 2 kW at frequency of 20 kHz. On this basis, together with experiments and finite element simulation on forming force with aluminum alloy sheet 1060, the results showed that the forming force reduced evidently by appropriate selection of amplitude and frequency, meanwhile, the change of them had a remarkable influence on plastic behavior which can be summarized into two opposite aspects: the softening and the hardening effect. When a lower amplitude and frequency was applied to the forming process, the softening effect dominated, leading to a decrease of forming force, however, under the application of a high-vibrating amplitude and frequency, the harden effect dominated resulting in the decline of plasticity and the increase of flow resistance.